THE ASSISTANCE OF DEVELOPING AN E-COMMERCE MARKETPLACE FOR MICRO, SMALL, AND MEDIUM MELINJO CHIP ENTERPRISES (MSMEs) IN SUKALABA, GUNUNG SARI, SERANG, BANTEN, INDONESIA - Abdul Bahits; Aria Cendana Kusuma; Fifin Tia Rohniati; Lismayada Wardani; Natalia Sari; Sri Yunita (Yayasan Education and Social Center, 2023)
Sukalaba is a village located in a mountainous area in the Gunungsari District, Serang, Banten. There are micro, small, and medium enterprises (MSMEs) that produce melinjo chips as the source of income of these entrepreneurs. One of the problems faced by these entrepreneurs is dividing the market share only at one distribution point, hence they only produce the chips on certain days, depending on the orders. Based on the problem mentioned, the authors conclude that the sales were stagnant and there were no significant changes, therefore the ways to increase sales are by increasing product variants and packaging, and utilizing technology in the form of an e-commerce marketplace, so that it has an even higher selling price. Through the utilization of an e-commerce marketplace as an initial step towards changes and developments, melinjo chip business can grow tremendously